2014
DOI: 10.1245/s10434-014-3933-x
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathologic Characteristics of Incidentally Identified Pheochromocytoma

Abstract: Half of patients presenting for surgical resection of pheochromocytoma were identified incidentally. These patients had equivalent rates of malignancy and pathologic traits associated with malignant potential and require definitive evaluation and early surgical referral.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
5
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 26 publications
1
5
0
Order By: Relevance
“…Thus, more highly concentrated stores of catecholamines in some tumors and associated higher rates of catecholamine secretion may contribute to why some patients with similarly sized PPGLs are diagnosed on the basis of signs and symptoms while others present as incidentalomas. This conclusion is consistent with other reports of lower indices of catecholamine production and secretion in patients with PPGLs presenting as incidentalomas than for other reasons (5,12).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Thus, more highly concentrated stores of catecholamines in some tumors and associated higher rates of catecholamine secretion may contribute to why some patients with similarly sized PPGLs are diagnosed on the basis of signs and symptoms while others present as incidentalomas. This conclusion is consistent with other reports of lower indices of catecholamine production and secretion in patients with PPGLs presenting as incidentalomas than for other reasons (5,12).…”
Section: Discussionsupporting
confidence: 93%
“…Whereas previously affected patients were mainly diagnosed based on signs and symptoms, today the tumors are increasingly found incidentally as part of imaging studies for purposes unrelated to suspicion of PPGL (6,11,12). Due to recognition of an increasing number of pathogenic mutations and a high rate of disease recurrence, PPGLs are now being found during surveillance screening in patients with a genetic predisposition or past history of disease (11).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies reported that patients with incidentally identified PPGLs had a lower prevalence of hypertension. 34,35 However, our study has several limitations. First, this was a retrospective study spanning a 6-year period.…”
Section: Discussionmentioning
confidence: 90%
“…12 This age disparity was attributed to a delay in diagnosis secondary to the atypical symptoms of incidentally identified pheochromocytoma patients. Conversely, in our study, the incidental aldosteronoma patients presented with typical symptoms, and a majority met the Endocrine Society criteria for a targeted workup for primary hyperaldosteronism based solely on the severity of hypertension or the presence of hypokalemia.…”
Section: Discussionmentioning
confidence: 99%